AI Hallucinations? What About Human Hallucination?! Addressing Human Imperfection Is Needed for an Ethical AI - Tlili, Ahmed; Burgos, Daniel (UNIR, 2026)
This study discusses how the human imperfection nature, also known as the human hallucination, could contribute to or emphasize technology (generally) and Artificial Intelligence (AI, particularly) hallucination. While the ongoing debate puts more efforts on improving AI for its ethical use, a shift should be made to also cover us, humans, who are the technology designer, developer, and user. Identifying and understanding the link between human and AI hallucination will ultimately help to develop effective and safe AI-powered systems that could have some positive societal impact in the long run.
Keywords: Artificial Hallucination; Ethics; Human Hallucination; Human-Machine Collaboration; Morals and Responsibility